Comparison of the Chloroplast Genome Sequences of 13 Oil-Tea Camellia Samples and Identification of an Undetermined Oil-Tea Camellia Species From Hainan Province - Chen, Jing; Guo, Yujian; Hu, Xinwen; Zhou, Kaibing (Frontiers in Plant Science, 2022)
The comparison of chloroplast genome (cpDNA) sequences among different plant species is an important source of plant molecular phylogenetic data. In this paper, the cpDNA sequences of 13 different oil-tea camellia samples were compared to identify an undetermined oil-tea camellia species from Hainan Province. The cpDNA of the samples was sequenced and resequenced, and divergence hotspots and simple sequence repeat (SSR) variations were analyzed. Bayesian inference (BI) and maximum-likelihood (ML) phylogenetic trees were constructed based on the full cpDNA sequences. The cpDNA sequences were 156512∼157089 bp in length and had the circular tetrad structure typical of angiosperms. The inverted repeats (IRs) of different species included varying contractions and expansions. The cpDNA sequences of the samples of the undetermined species of oil-tea camellia from Hainan Province and Camellia gauchowensis from Xuwen County were identical. In total, 136 genes were annotated, including 91 protein-coding genes (PCGs), 37 tRNA genes and 8 rRNA genes. The GC content of the cpDNA was 37.3%. The small single-copy (SSC)/IR boundary was rich in variation. Divergence hotspots were mainly located in the intergenic space (IGS) and coding sequences (CDSs), and there were obvious differences in divergence hotspots among species. The same divergence hotspots were found in Camellia vietnamensis, Camellia gauchowensis and the undetermined species of oil-tea camellia from Hainan Province. A total of 191∼198 SSR loci were detected. Most of the SSRs included A or T, and the distribution of SSRs in the cpDNA was uneven. Different species shared common SSRs and exhibited unique SSRs. Based on the full cpDNA sequences, the evolutionary relationships of different species of Camellia were well identified. The thirteen samples were classified into 2 clades and 6 subclades, and the different sections of Camellia clustered on the same branch in 2 clades and 2 subclades. Camellia vietnamensis was more closely related to the undetermined species of oil-tea camellia from Hainan Province and the sample of Camellia gauchowensis from Xuwen County than to the sample of Camellia gauchowensis from Luchuan County. Camellia osmantha was closely related to Camellia gauchowensis and Camellia vietnamensis. In conclusion, the cpDNA of different oil-tea camellia species has a conserved tetrad structure with certain length polymorphisms. SSRs are expected to be developed as “barcodes” or “identity cards” for species identification. SSR variations and other factors result in abundant divergence hotspots in the CDSs and IGS (one non-CDS region), indicating that full cpDNA sequences can be used for the species identification and phylogenetic analysis of Camellia. Accordingly, the undetermined species of oil-tea camellia from Hainan Province is likely Camellia vietnamensis, Camellia vietnamensis and Camellia gauchowensis may be the same species, and additional genetic evidence is needed to determine whether Camellia osmantha is a new independent species. The previous division of related sections of Camellia may need readjustment based on full cpDNA sequences.